2014
DOI: 10.1111/bju.12447
|View full text |Cite
|
Sign up to set email alerts
|

Occult lymph node metastases in patients with carcinoma invading bladder muscle: incidence after neoadjuvant chemotherapy and cystectomy vs after cystectomy alone

Abstract: Objective• To investigate the effect of neoadjuvant chemotherapy (NAC) on the incidence of lymph node (LN) metastases in clinically node-negative (cN0) patients with carcinoma invading the bladder muscle (MIBC). Patients and Methods• Between 1990 and 2012, 828 consecutive patients underwent radical cystectomy (RC) with extended pelvic LN dissection (ePLND), of whom 441 had cT2-4N0M0 stage disease. • A total of 83 patients received NAC then underwent RC and 358 patients underwent RC only. The ePLND template and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 30 publications
(51 reference statements)
1
25
0
2
Order By: Relevance
“…The median (interquartile range [IQR]) age of our cohort at time of RC was 64 (57-71) years. The median (IQR) number of positive LNs was 2 (1-5), with a median (IQR) number of LNs removed of 20 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). These clinicopathological characteristics were similar in the NAC and AC groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median (interquartile range [IQR]) age of our cohort at time of RC was 64 (57-71) years. The median (IQR) number of positive LNs was 2 (1-5), with a median (IQR) number of LNs removed of 20 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). These clinicopathological characteristics were similar in the NAC and AC groups.…”
Section: Resultsmentioning
confidence: 99%
“…Further, although studies have identified that pathological responders to NAC have better outcomes than non-responders, the comparison of NAC non-responders with chemotherapy-na€ ıve non-responders has not been well characterised [19]. Another study reported on the incidence of LN metastases in clinically non-metastatic patients comparing those treated with NAC vs RC alone, but focused on the effect of NAC upon the likelihood of LN metastases rather than the outcomes of the 16 LN-positive NAC patients [20].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, neoadjuvant chemotherapy has not been performed regularly (22). Moreover, because neoadjuvant chemotherapy targets micrometastasis (including LN metastasis), patients with LN metastases are likely to benefit from this therapy (23).…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to a recently reported single institution study examining ypN status in patients undergoing an extended pelvic lymph node dissection post-NAC. 22 Survival in the present series is related to the absence or presence of lymph node metastases, which is also correlated with clinical stage. NAC did not have a meaningful impact on survival for patients with pN+ disease, but it is possible that NAC down-staged patients such that the incidence of pN+ disease is reduced which contributes to the improvement in survival observed with NAC.…”
Section: Discussionmentioning
confidence: 54%